Population trends in prenatal detection of transposition of great arteries: impact of obstetric screening ultrasound guidelines. (4th May 2018) - Ravi, P.; Mills, L.; Fruitman, D.; Savard, W.; Colen, T.; Khoo, N.; Serrano‐Lomelin, J.; Hornberger, L. K.
ABSTRACT: Objectives: Dextro‐transposition of the great arteries (d‐TGA) is one of the most common critical neonatal heart defects, with a low detection rate antenatally. We sought to evaluate trends in the prenatal detection of d‐TGA with or without ventricular septal defect (VSD) in Alberta over the past 13 years, examining the potential impact of ultrasound guidelines incorporating screening of cardiac outflow tracts, updated in 2009–2010 and in 2013, and factors affecting detection of the condition. Methods: All fetuses and neonates with d‐TGA, with or without VSD, encountered between 2003 and 2015 in the province of Alberta, were identified retrospectively. Clinical records including obstetric ultrasound reports were reviewed. Pregnancy outcome, common referral indications and associated maternal and fetal pathology in affected pregnancies were assessed. Results: From 2003 to 2015, 127 cases with d‐TGA were encountered in Alberta, of which 47 (37%) were detected prenatally. Prenatal detection improved over the study period, from 14% in 2003–2010, to 50% in 2011–2013, and to 77% in 2014–2015. Of the 47 fetuses with a prenatal diagnosis of d‐TGA, an indication for fetal echocardiography included abnormal or poorly visualized cardiac outflows with normal four‐chamber view in 46 (98%). Comorbidities were identified in 12 mothers, only five of which represented an additional reason for fetal echocardiography referral, and four fetuses had extracardiac pathology. Conclusion: Substantial improvement in the prenatal detection of d‐TGA has been observed in Alberta over the past few years, owing to improved screening of cardiac outflow tracts on routine obstetric ultrasound examination in otherwise healthy pregnancies, and has been temporally associated with updated obstetric ultrasound guidelines suggesting that these contributed to optimized screening of affected pregnancies. Copyright © 2017 ISUOG. Published by John Wiley & Sons Ltd.